Senegal - land, climate, energy, agriculture and development: A study in the Sudano-Sahel Initiative for regional development, jobs, and food security - Amy Faye; Mohamadou Dièye; Pape Bilal Diakhaté; Assane Bèye; Moussa Sall; Mbaye Diop (University of Bonn, Center for Development Research (ZEF), 2021)
Located in West Africa, Senegal is classified as a least-developed country that has historically had political stability and slow economic growth compared to the rest of Sub-Saharan Africa (SSA). However, from 2012 onward, a new government has adopted new policies (infrastructure investments, liberalization of the groundnut sector and opening of the energy sector) to enhance economic growth and governance. Senegal thus experienced significant improvements in the period from 2012 to 2015. Future economic growth in Senegal can be significantly shaped by the energy sector regarding the recent oil and gas discoveries if the common resource curse can be avoided. The country is characterized by a poverty rate of 38 percent and fairly stable food security, with only 7.2 percent of the population being food insecure. However, some localized pockets of acute food needs remain. This is in part linked to agricultural production (the main source of income and labor), which depends highly on climatic hazards. Moreover, production resources such as land are highly vulnerable to climatic and anthropogenic factors. The country has a good access rate to electricity and safe water. However, access to electricity is unequal, with rural lagging behind urban areas. [...] The evaluation of key policies, the Intended Nationally Determined Contribution for climate governance, the PRACAS (for agriculture and food security) and land-use policies highlights the main factors for success and failure and identifies key challenges that the government of Senegal needs to pay close attention to in order to ensure greater policy design and implementation success in the future. The main challenges are related to governance, funding and monitoring and evaluation. In terms of governance, it is important to ensure the participatory design and implementation of the policies to foster stakeholders' ownership and thus facilitate their implication. As for funding, the key is to avoid building policy objectives based on unsecured funding by making realistic plans based on already secured funding (if possible, from the national budget). Finally, in terms of monitoring and evaluation, it is key to ensure the sustained availability of good-quality statistical data to allow better targeting of areas in which to intervene, better allocation of financial resources and better assessment of gaps, progress, and impact.
Keywords: O30; Q24; Q25; Q42; Q54; Q55; Q58; 330; Sahel; energy; climate change; land degradation; innovation; policy